MEMBANGUN SISTEM INFORMASI PENGOLAHAN DATA DURASI WAKTU (SIPANDU) DI DPMPTSP KOTA SURAKARTA DENGAN FRAMEWORK CODEIGNITER - Ahmad Setiawan (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2019)
DPMPTSP Surakarta is a government institution of Surakarta. It serves licensing and investment in Surakarta. One indicator of success from licensing services is assessed by the duration of service. At this time, the data processing duration of licensing service is still semi-manual. The employees must import data from the system database using Navicat software and have to process it in Microsoft excel. Therefore, the duration of data processing for the licensing service takes a long time with around 8 minutes for each. The aims of this study is to design an information system for duration of processing data and abbreviated as SIPANDU in DPMPTSP Surakarta. This research is also expected to accelerate and assist the process of duration data processing for licensing services in the DPMPTSP Surakarta. The method of data collection covered interviewing, observing, and studying literature while the system development method used the waterfall method. User satisfaction testing used the webqual method and it shows that usability quality has influence on user satisfaction since the significance value is 0.006 <0.05. The quality of information has an influence on user satisfaction because the significance value is 0.009 <0.05. Moreover, the interaction quality has no effect because its significance value is 0.814> 0.05. However, three variables influence user satisfaction since the significance value is